Theoretical and Practical Aspects regarding the Duties of the President of Romania in the Procedure of Naming the Government – Part II - Oana ŞARAMET (Bulletin of the Transilvania University of Braşov • Vol. 14 (63) • No. 2 - 2021 • Series VII, 2021)
During the second part of this study, we aim to analyse other aspects regarding the duties of the Romanian President in the procedure of appointing a Government, particularly in regard to naming the candidate for the office of prime minister, thus referencing the potential situations which can occur in the exercise of these duties according to the constitutional regulations in force. We will also express a point of view in regard to the particular situation which is currently developing on our political stage. We will also consider constitutional regulations specific to other European states so as to point out possible solutions of constitutional revise in order to prevent or even avoid such political crisis in the future.
Keywords: head of state; candidate; prime-minister; vote of confidence; Government